Transformation of Social Identity Among Former Thugs in Surakarta City: Self-Navigation within Religious Communities - Warsito (Jurnal Sosiologi Agama, 2025)
This article examines the transformation of the social identity of former gangsters (preman) in the city of Solo who seek to rebuild their religious identity through the process of hijrah and active participation in religious communities such as Juba Rescue and Ekspreso. The study employs the Social Identity Theory (Tajfel & Turner) and the Stigma and Identity Management Theory (Erving Goffman) to understand the dynamics of self-transformation and the strategies used to manage a spoiled identity. Data were collected through in-depth interviews, participant observation, and field documentation conducted between 2023 and 2024. The findings reveal that the transformation of former gangsters’ social identity unfolds across five main dimensions: (1) Social Identity Repositioning — from Gangster to Respected Muslim; (2) Symbolic Representation and Self-Presentation; (3) Spiritual Process and Moral Transition; (4) Ideological and Social Loyalty Shifts; and (5) Economic Reorientation and the Emergence of a New Work Ethic. This process illustrates a continuous negotiation between a deviant past and the construction of a renewed religious self, highlighting the success of stigma management in shaping a new social identity within the urban public sphere.